A comparison of the effects of plyometric and virtual training on physical and functional performance: a randomized, controlled, clinical trial - Lobato, Daniel F; Teixeira, Vitória A; Froes, Isabelle; Donzeli, Marina A; Bertoncello, Dernival (The Journal of sports medicine and physical fitness, 2021)
This study compared the effects of plyometric training (PT) and virtual training (VT) on physical and functional performance. Fifty-five moderately-trained women participated in this randomized, controlled, prospective study. The subjects were randomly assigned to VT (N.=20), PT (N.=18), and control (CG, N.=17) groups. The VT was performed using the Your Body Shape Fitness Evolved 2012 exergame in an Xbox360/Kinetic environment. The PT was based on the methods used in previous studies. Both interventions were performed 3 times per week for 8 weeks. Participants in the CG were not submitted to any type of intervention. Physical performance (fitness and athleticism levels) was assessed using the Nike+ Kinetic Training exergame in an Xbox360/Kinetic environment. Functional performance was assessed using the shuttle run (SR), triple hop test (THT), and six-meter timed hop test (STHT). Postintervention fitness and athleticism levels were significantly greater in VT (P<0.001 and P=0.009) and in PT (P<0.001 and P=0.003) than baselines values. Only VT postintervention fitness level was significantly greater compared to CG (P=0.03). Postintervention SR values were significantly lower than baselines values in all groups (P<0.001). VT (P=0.08) and PT (P=0.006) postintervention values were significantly lower compared to CG. Postintervention THT values were significantly greater than baselines values in VT and PT (P<0.001). VT (P=0.04 - dominant limb) and PT (P=0.003 - dominant limb; and P=0.03 - non-dominant limb) postintervention values were significantly greater compared to CG. Postintervention STHT values were significantly lower than baselines values in VT (P<0.001), PT (P<0.001) and CG (P=0.01-0.02). PT postintervention dominant (P=0.01) and non-dominant (P=0.03) limb values were significantly lower compared to CG. Both VT and PT are beneficial for improving physical and functional performance. Therefore, VT might be a new tool that can be used for physical exercise practice and conditioning training in moderately-trained women.